2020
DOI: 10.21203/rs.3.rs-25286/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Natural Course of Hereditary Angioedema in a Chinese Cohort

Abstract: Background Hereditary angioedema (HAE) is a rare disease with potential life-threatening risks. Until now, few studies have focused on the natural course of HAE, which is essential for practitioners and patients to predict disease progression and avoid possible risk factors. Objectives Describe the natural course of HAE and explore possible risk factors, providing new clues for guiding clinical prevention and treatment. Methods A web-based survey was conducted in 103 Chinese patients with type 1 HAE. Diseas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…About half of patients had not experienced edema for at least 1 month prior to sampling. All the patients were stratified based on the annual mean frequency of abdominal attacks and laryngeal edema, and the proportion of the patients with frequent gastrointestinal angioedema (49.1%) was higher than in our previous study 10 .…”
Section: Demographic and Clinical Characteristics Of Patientsmentioning
confidence: 84%
See 2 more Smart Citations
“…About half of patients had not experienced edema for at least 1 month prior to sampling. All the patients were stratified based on the annual mean frequency of abdominal attacks and laryngeal edema, and the proportion of the patients with frequent gastrointestinal angioedema (49.1%) was higher than in our previous study 10 .…”
Section: Demographic and Clinical Characteristics Of Patientsmentioning
confidence: 84%
“…Thus, natural questions include whether alterations of the gut microbiome occur in HAE patients, whether bacterial biomarkers can be identified to detect recent HAE episodes, and whether there are differences in the microbiomes of patients with mild and severe HAE. The interquartile range for gastrointestinal and laryngeal edema in Chinese HAE patients was 0-5 and 0-2 times per year respectively 10 . Therefore, patients were divided into two groups based on the average number of abdominal attacks per year prior to medication: those with significant gastrointestinal angioedema (≥5 attacks per year) and those with infrequent gastrointestinal angioedema (<5).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…25 The mean delay in diagnosis of HAE for Chinese patients could be even longer (12.64 years). 26 A study showed the Chinese HAE patients usually needed to consult 6 doctors before getting a confirmed diagnosis; their most frequently visited departments included emergency (90.6%), dermatology (71.9%), allergy (61.5%), gastroenterology (52.1%), rheumatology (34.4%), and otolaryngology (34.4%). 27 For the 2 HAE patients identified in our cohort, they both had received systemic corticosteroids for many times and had delayed diagnosis up to 25 years.…”
Section: Discussionmentioning
confidence: 99%